Pelaksanaan Penetapan Lokasi Tanah Milik Masyarakat Untuk Pembangunan Kepentingan Umum - Edith Ratna M.S.; Sangga Yulia Sudrajat (Magister Kenotariatan Universitas Diponegoro, 2022)
The consideration of the implementation of this research is that there are problems that arise in land owners who are the object of land acquisition for development for the public interest, as a result of the provisions of Article 27 paragraph 3 of Law No. 2 of 2012 concerning Land Acquisition for Development for Public Interest, which is essentially